Analysis of Encapsulation Efficiency Bacillus sp. Based Variations in Sodium Alginate Concentration in the Beads - Mochammad Mirza Saputra; Yenny Wuryandari; Noni Ramadhini (Future Science, 2023)
The use of biological agents such as Bacillus sp. Bacteria have started to be widely used by farmers as a new form of control. Bacillus sp. needs to require a special method in its application because it has certain living conditions, and Bacillus sp. is susceptible to environmental stress like other microorganisms. Apply Bacillus sp. as a biological control agent in the field, it needs to be formed into a formulation to be more effective and efficient when applied. Liquid formulations often used cannot maintain the viability of bacteria in the soil. The bioencapsulation formulation in the form of microcapsules is considered more effective in maintaining the viability of bacteria in the soil. This study aims to determine the effect of concentration on the encapsulation efficiency of Bacillus sp. inside the microcapsule. Beads are made using the extrusion method by combining a sodium alginate suspension of 1%, 1.5%, and 2% concentration and a bacterial suspension and dropping it into a calcium chloride solution. The encapsulation efficiency test was carried out once by extracting the bacteria on the beads, growing them in the growth medium, and then observing them. The results of the encapsulation efficiency test with a concentration of 1%, 1.5%, and 2% had values of 1%, 0.36%, and 1.35%, respectively. The difference in the results of this encapsulation efficiency indicates that there is an effect of sodium alginate concentration on the value of encapsulation efficiency.